A popularização da ciência em uma universidade comunitária : as reverberações dos projetos de pesquisa na ótica do pesquisador - Piccoli, Marcia Speguen de Quadros (My University, 2023)
This thesis research was developed with the objective of identifying the perception of the popularization of science by researchers who are CNPq Research Productivity Scholarship holders, from a Community Higher Education Institution - ICES, in relation to its research projects, to identify indicators that favor the process of interaction between science and common sense. The mobilizing question of the study received the following formulation: Which indicators can favor the practice of popularization of science in the Higher Education Institutions, considering the perception on the subject, on the part of the reserachers who are scholarship holders of productivity in research of the CNPq of a communitarian institution of higher education? The theoretical background that supported the study was based on the concept of opening to dialogue of Paulo Freire (1967; 1983; 1987; 1996; 1999); on the dimensions of analysis related to the anatomy of the Institutions of Higher Education (value, function and interaction) presented by Tristan McCowan (2015; 2016; 2017; 2018), and on the role of science in the contemporary social context suggested by Boaventura de Souza Santos (2003; 2007; 2008; 2009; 2018). Several procedures have been adopted to delimitate the object of research in question, among which, the systematic review of literature (Akobeng, 2005; Vosgerau and Romanowski, 2014 and Costa and Zoltowski, 2014), the narrative interviews, guided by Moraes (2002, 2003, 2003a) and Stecanela (2012) and the discursive textual analysis, as proposed by Moraes and Galiazzi (2007). The research sample involved the participation of ten researchers who are CNPq Scientific Productivity Scholarship holders of an ICES, out of a total of 28 professors, through invitation and spontaneous participation. From the analyzed narratives, five categories emerged; they revealed the observation of researchers in a movement of self perception, perception of the other, a critical view on the popularization of science, on the management of the popularization of science and reflexivity on learning in the trajectory of the researcher. These categories, coming from empirical material, in line with the theories accessed and investigative authorship, provide the suggestion of three indicators for the popularization of science: a) knowledge management; b) scientific culture and c) cooperation. These results favor the defense of the thesis on the need for policies that promote the popularization of science in the ICES, as Community institutions that advocate the common good, in order to induce this practice through the valorization, support and recognition of the important and indispensable interaction between science and common sense. [resumo fornecido pelo autor]
Esta pesquisa de tese foi desenvolvida com o objetivo de identificar a percepção da popularização da ciência por parte dos pesquisadores com Bolsa de Produtividade em Pesquisa do CNPq, de uma Instituição de Ensino Superior Comunitária - ICES, em relação aos seus projetos de pesquisa, para identificar indicadores que favoreçam o processo de interação entre a ciência e o senso comum. A pergunta mobilizadora do estudo acolheu a seguinte formulação: Quais indicadores podem favorecer a prática da popularização da ciência nas Instituições de Ensino Superior, considerando a percepção sobre o tema, por parte dos pesquisadores bolsistas de produtividade em pesquisa do CNPq de uma instituição de ensino superior comunitária? O embasamento teórico que sustentou o estudo foi fundamentado pelo conceito de abertura para o diálogo de Paulo Freire (1967; 1983; 1987; 1996; 1999); pelas dimensões de análise relacionadas à anatomia das Instituições de Ensino Superior (valor, função e interação) apresentadas por Tristan McCowan (2015; 2016; 2017; 2018) e sobre o papel da ciência no contexto social contemporâneo proposto por Boaventura de Souza Santos (2003; 2007; 2008; 2009; 2018). Vários procedimentos foram adotados para o cercamento do objeto de pesquisa em questão, entre os quais, a revisão sistemática de literatura (Akobeng, 2005; Vosgerau e Romanowski, 2014; Costa e Zoltowski, 2014), as entrevistas narrativas, orientadas por Moraes (2002, 2003, 2003a) e Stecanela (2012) e a análise textual discursiva, conforme proposta por Moraes e Galiazzi (2007). A amostra da pesquisa envolveu a participação de dez pesquisadores com Bolsa de Produtividade Científica do CNPq de uma ICES, de um total de 28 docentes, por meio de convite e adesão espontânea. Das narrativas analisadas emergiram cinco categorias que revelaram a observação dos pesquisadores em um movimento de percepção de si, do outro, um olhar crítico sobre a popularização da ciência, sobre a gestão da popularização da ciência e de reflexividade sobre as aprendizagens na trajetória de pesquisador. Essas categorias, advindas do material empírico, em consonância com as teorias acessadas e a autoria investigativa, propiciam a sugestão de três indicadores para a popularização da ciência: a) gestão do conhecimento; b) cultura científica e c) cooperação. Esses resultados favorecem a defesa da tese sobre a necessidade de políticas que fomentem a popularização da ciência nas ICES, enquanto instituições comunitárias que preconizam o bem comum, de modo a induzir essa prática por meio de valorização, apoio e reconhecimento da importante e indispensável interação entre a ciência e o senso comum. [resumo fornecido pelo autor]
Keywords: Popularização da Ciência; Senso Comun; Diálogo; Instituição Comunitária de Ensino Superior; Gestão do Conhecimento; Popularization of Science; Common Sense; Dialogue; Community Institution ofHigher Education; Knowledge Management.